Hubungan Kemampuan Kerja, Kepuasan Kerja dan Disiplin Kerja dengan Kinerja Pegawai Dinas Pasar Kota Semarang - Yuniarti, Afit; Hariani, Dyah; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
This study aims are to determine the relationship of work ability, job satisfaction and job performance discipline of Dinas Pasar Kota Semarang. The method used in this study is a research eksplanatory. Samples are taken at random sampling. Sample in this study of 75 respondents. Data analysis techniques using quantitative data analysis. Â The findings of the research results show that Â The results of this study indicate that the hypothesis that states there is a positive relationship between the variables work ability, job satisfaction and work discipline against officers acceptable performance significantly with the coefficient of determination of work ability, job satisfaction and job performance of official discipline is at a 85.4% pregnancy meaning that the magnitude of the influence of a given work ability, job satisfaction and work discipline on the performance of officers is at 85.4%. While the remaining 14.6% taker is the influence of other variables work ability, job satisfaction and work discipline. Â The results of these studies indicate a positive and significant relationship between the variables work ability, job satisfaction and work discipline on the performance of the officer. This means to improve the performance of Dinas Pasar Kota Semarang can be done by making the procedure or standard of work that can be understood and implemented by all officers, personnel arrangement adapted to the educational background, increased participation in education and training of officers, the need for the provision of benefits are adjusted membership / function, granting performance awards to officers, awarding sanctions for officials who violate discipline, increased surveillance stick (waskat).